Magnetic sensitivity modeling of dual gate MOS transistor - Mohamed Kessi; Arezki Benfdila (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
In this paper, the magnetic field effect on the carrier transport phenomenon in the double gate metal-oxide-semiconductor field-effect transistor (MOSFET) has been investigated. This is done by exploring the Lorentz force and the behavior of a semiconductor subjected to a constant magnetic field. The magnetic field modulates the electrons position and density as well as the potential distribution in the case of silicon tunnel tunneling field-effects (FETs). This modulation impacts the device electrical characteristics such as ON current (ION), subthreshold leakage current (IOF), threshold voltage (VT), magneto-transconductance (gmm) and output magneto-conductance (gmDS). In addition, a hall voltage (VH) is induced and modulated by the magnetic field. It has been observed that this voltage influences the effective applied gate voltage. It has been observed that the threshold voltage variations induced by the magnetic field is of paramount importance and affects the device switching properties both speed and power dissipation, noted that the threshold voltage VT and (Ion/Iof) ratio are reduced by 10-3V and 102 for a magnetic field of ±6 and ±5.5 Tesla, respectively. We have simulated the different behavior in the channel, mainly doping concentration, potential distribution, conduction and valence bands, total current density, total charge density, electric field, electron mobility, and electron velocity.